Circadian Rhythm Disruption Influenced Hepatic Lipid Metabolism, Gut Microbiota and Promoted Cholesterol Gallstone Formation in Mice - He, Chuanqi; Shen, Weiyi; Chen, Chaobo; Wang, Qihan; Lu, Qifan; Shao, Wentao; Jiang, Zhaoyan; Hu, Hai (Frontiers in Endocrinology, 2021)
Background. Hepatic lipid metabolism regulates biliary composition and influences the formation of cholesterol gallstones. The key enzymes in liver are regulated by circadian rhythm related transcription factors. This study aimed to investigate the impact of circadian rhythm disruption on hepatic cholesterol and bile acid metabolism and the incidence of cholesterol stones formation. Methods. Male adult C57B/6J mice were fed with either lithogenic diet (LD) only during the sleep phase (time-restricted lithogenic diet feeding, TRF) or with LD ad libitum (non-time restricted lithogenic diet feeding, nTRF) for 4 weeks. Food consumption, body weight gain, and incidence of gallstone were measured. Metabolic variables in blood, lipid accumulation in the liver, circadian expression of clock and metabolic genes in the liver and gut microbiota were analyzed. Results. TRF induced circadian rhythm disorganization in mice, which led to significant differences in the expression levels diurnal patterns of clock-related genes. In TRF -fed mice, the circadian rhythm of expressions of genes related with bile acid and cholesterol metabolism was disrupted. The diurnal rhythm of gut microbiota was affected as well. These changes were related with increase of cholesterol content in bile, which resulted in more aggravation of gallstones in TRF-fed mice. Conclusion. Circadian rhythm disorder led to abnormal metabolism of hepatic bile acid and cholesterol in mice, promoting gallstone formamation.